(untitled) (Journal of actual problems of jurisprudence, 2019)
On the basis of the analysis of ancient sources, pre-revolutionary and modern works of domestic scientists-lawyers experience of research of an origin of the property right and other legal forms of possession property, their structurization depending on level of material living conditions and development of individual freedom of citizens reveals.